Perancangan Brand dan Publisitas Padepokan Seni Topeng Asmorobangun untuk Meningkatkan Ekuitas Merek - Aditya Nirwana; Etsa Astridya Setiyati (AKSA: Jurnal Desain Komunikasi Visual, 2018)
Wayang Topeng Malangan is a valuable cultural asset with various potentials for the development of the nation's character, but the many people in Malang are still unaware. Getting to understand the studio is the entrance for the people to understanding Wayang Topeng Malangan, one of which is Padepokan Seni Topeng Asmorobangun. The aim of this research is to obtain a visual marketing communication design in the form of Asmorobangun brand, that can increase brand equity, as well as marketing media that can become a medium of information for Malang city people to understanding Wayang Topeng Malangan. With a customer-based marketing strategy (STP), and marketing mix (4P), the results is is the concept of design in the form of 'millenial', progressive, democratic, popular, which in itself offers value in a more progressive form. With visualizations communicating those positions, it is expected to foster brand equity in the target market of young people (men and women) at 18-25 years old, attend high school or college, be educated, familiar with technology, internet, and popular culture. Visualization of the concept, obtained brand identity such as logo, corporate color, typography, photography, illustrations, and supporting elements, and all of that implemented at ; 1) Poster; 2) Roll Banner; 3) Stationery; 4) Social media advertising; 5) Business Cards; 6) Corporate Identity System (CIS); 2) Site; and 3) Photo Books.